2017
DOI: 10.3390/ijms18051077
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm is a Major Virulence Determinant in Bacterial Colonization of Chronic Skin Ulcers Independently from the Multidrug Resistant Phenotype

Abstract: Bacterial biofilm is a major factor in delayed wound healing and high levels of biofilm production have been repeatedly described in multidrug resistant organisms (MDROs). Nevertheless, a quantitative correlation between biofilm production and the profile of antimicrobial drug resistance in delayed wound healing remains to be determined. Microbial identification, antibiotic susceptibility and biofilm production were assessed in 135 clinical isolates from 87 patients. Gram-negative bacteria were the most repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 103 publications
(133 reference statements)
7
68
2
2
Order By: Relevance
“…However, many current studies have reported increasing resistance to imipenem and ciprofloxacin. Di-Domenico et al [10] found A. baumannii isolates from patients with colonized skin ulcers to have 75% resistance to imipenem, 75% resistance to trimethoprim-sulfamethoxazole, and 91% resistance to ciprofloxacin. Addi-Ali et al [12] showed 92% of A. baumannii clinical isolates to be resistant to ciprofloxacin and 68% to be resistant to imipenem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many current studies have reported increasing resistance to imipenem and ciprofloxacin. Di-Domenico et al [10] found A. baumannii isolates from patients with colonized skin ulcers to have 75% resistance to imipenem, 75% resistance to trimethoprim-sulfamethoxazole, and 91% resistance to ciprofloxacin. Addi-Ali et al [12] showed 92% of A. baumannii clinical isolates to be resistant to ciprofloxacin and 68% to be resistant to imipenem.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the biofilmforming ability of A. baumannii strains to be related to major virulence factors, promoting bacterial persistence and chronicity in a specific manner, distinct from the MDR phenotypes. In addition, quorum sensing, which is a communication mechanism used by bacteria to recognize population density fluctuations and control gene expression [7], has been shown to be associated with biofilm formation by A. baumannni [8][9][10]. Among the different A. baumannii virulence factors, the most important is their ability to produce biofilms and their survival in hospital environments, which is related to their high degree of antibiotic resistance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The range of antibiotics tested is listed in the additional files section (Additional file 1). Strains were classified as MRSA when presenting both oxacillin resistance (MIC ≄4 mg/ml) and positive agglutination test for Penicillin-Binding Protein (PBP2, Oxoid, Basingstoke, UK) [76].…”
Section: Microbiological Diagnosismentioning
confidence: 99%
“…However, in that study they could not detect a correlation between MDR or non-MDR Pseudomonas aeruginosa and the strength of attachment to stainless steel surfaces. In another study, Di Domenico et al (2017) observed that 80% of clinical isolates were able to form biofilm. For these strains, the level of biofilm production between MDR isolates and non-MDR isolates was comparable and no significant difference was detected.…”
Section: Discussionmentioning
confidence: 96%
“…In another study, Di Domenico et al . () observed that 80% of clinical isolates were able to form biofilm. For these strains, the level of biofilm production between MDR isolates and non‐MDR isolates was comparable and no significant difference was detected.…”
Section: Discussionmentioning
confidence: 99%